Corneal aberrations measured with a high-resolution Scheimpflug tomographer: repeatability and reproducibility. Issue 4 (April 2020) - McAlinden, Colm; Schwiegerling, Jim; Khadka, Jyoti; Pesudovs, Konrad
Abstract : The Pentacam HR provided highly precise aberration outputs. The most precise measurements are achievable with the cornea fine measurement mode and wavefront aberrations. Abstract : Purpose: To evaluate the precision of elevation and wavefront aberration measurements with the Pentacam HR (Oculus Optikgeräte GmbH). Setting: Flinders University, Australia. Design: Instrument evaluation study. Methods: A randomly selected eye of 100 participants was scanned twice with the Pentacam HR by 1 observer on the 3 measurement modes: 25-picture, 50-picture, and cornea fine. A second observer performed 2 scans on the same random eye with the 25-picture mode. Repeatability and reproducibility were assessed using the within-subject SD (Sw ) statistic from a 1-way analysis of variance. Results: From the 100 scanned eyes, the higher-order aberration root mean square (RMS) repeatability limit ( S W × 1.96 2 ) for both elevation and wavefront, and anterior and posterior measurements was 0.03 μm for all 3 measurement modes. Anterior, posterior, and total corneal wavefront Zernike terms were highly precise, with most Zernike terms displaying a repeatability limit of 0.03 μm. The least repeatable measurement was the posterior elevation Zernike term Z 1 − 1 with the 25-picture scan (repeatability limit 1.50 μm). The cornea fine measurement mode provided the most precise measurements. Reproducibility limits (second observer) were similar to repeatability limits with the 25-picture scan mode. Conclusions: The Pentacam HR provided highly precise aberration outputs. The most precise measurements are achievable with the cornea fine measurement mode and wavefront aberrations. One should be cognizant of posterior elevation aberration precision, particularly for lower radial order and higher azimuthal frequency terms. Accounting for tilt and misalignment of aberrations, all RMS and Zernike aberrations were extremely precise (repeatability and reproducibility limit less than 0.000001 μm).